Research on the methods for calculating the width of the approach channel to the port - Paulauskas, Vytautas; Paulauskas, Donatas; Plačienė, Birutė; Barzdžiukas, Raimondas; Pridotkas, Gintaras; Maksimavičius, Ričardas; Jankowski, Stefan (Transport, 2019)
An approach channel to the port is a very important part of port infrastructure ensuring navigational safety of the ships entering and departing the port. Various methods used for determining the width of the approach channel to the port provide different results. Sometimes, variations are significant and make difficulties in arriving at the correct final decision. The article analyses diverse methods for research on calculating the width of the approach channel to the port. The obtained results have been verified conducting a real experiment involving real ships passing under similar hydro-meteorological conditions. The evaluation of the results and recommendations presented in the article can be used for the optimization and design of approach channels to ports.